ZC4H2 stabilizes RNF220 to pattern ventral spinal cord through modulating Shh/Gli signaling. (23rd July 2019) - Ma, Pengcheng; Song, Ning-Ning; Cheng, Xiaoning; Zhu, Liang; Zhang, Qiong; Zhang, Long long; Yang, Xiangcai; Wang, Huishan; Kong, Qinghua; Shi, Deli; Ding, Yu-Qiang; Mao, Bingyu
Abstract: ZC4H2 encodes a C4H2 type zinc-finger nuclear factor, the mutation of which has been associated with disorders with various clinical phenotypes in human, including developmental delay, intellectual disability and dystonia. ZC4H2 has been suggested to regulate spinal cord patterning in zebrafish as a co-factor for RNF220, an ubiquitin E3 ligase involved in Gli signaling. Here we showed that ZC4H2 and RNF220 knockout animals phenocopy each other in spinal patterning in both mouse and zebrafish, with mispatterned progenitor and neuronal domains in the ventral spinal cord. We showed evidence that ZC4H2 is required for the stability of RNF220 and also proper Gli ubiquitination and signaling in vivo . Our data provides new insights into the possible etiology of the neurodevelopmental impairments observed in ZC4H2-associated syndromes.